CRITICAL ORIENTATION IN BRIDGING MATHEMATICAL AND FOOD SECURITY LITERACY THROUGH PROBLEM-BASED STEAM-H - Fatimah, Ai Tusi; Isyanto, Agus Yuniawan; Erlin, Euis; Andriana, Bibin Bintang (LPPM Universitas Jambi, 2026)
The increasing complexity of food security challenges requires vocational education to equip students with the ability to integrate mathematical reasoning and sustainability-oriented decision-making. However, previous studies have generally examined Mathematical Literacy and Food Security Literacy as separate competencies, resulting in a limited understanding of how these literacies interact within vocational learning contexts. This study aimed to investigate the effectiveness of Problem-Based Instruction integrated with the STEAM-H (Science, Technology, Engineering, Agriculture, Mathematics, and Health) framework in enhancing vocational students’ Mathematical Literacy, Food Security Literacy, and Critical Orientation. A convergent mixed-methods design was employed involving 24 eleventh-grade agribusiness vocational students. Quantitative data were collected through pretest–posttest holistic evaluation tests, while qualitative data were obtained concurrently through classroom observations and semi-structured interviews. The results revealed significant improvements in Mathematical Literacy and Food Security Literacy, accompanied by qualitative evidence indicating a shift from procedural computation toward evidence-based and sustainability-oriented decision-making. Three dimensions of Critical Orientation emerged from the qualitative findings, namely Cognitive Transition, Critical Disposition, and Comprehensive Critical Synthesis. The novelty of this study lies in conceptualizing Critical Orientation as a bridging construct connecting Mathematical Literacy and Food Security Literacy within a Problem-Based STEAM-H learning environment. These findings contribute to interdisciplinary literacy theory and provide practical implications for designing vocational curricula that promote higher-order thinking, sustainability awareness, and workforce readiness.